Local and systemic delivery of mRNA encoding survivin-T34A by lipoplex for efficient colon cancer gene therapy - Zhang X (Dove Medical Press, 2019)
Xueyan Zhang,1 Ke Men,1 Yuanfa Zhang,1 Rui Zhang,1 Li Yang,1 Xingmei Duan21State Key Laboratory of Biotherapy and Cancer Center/Collaborative Innovation Center for Biotherapy, West China Hospital, Sichuan University, Chengdu 610041, People’s Republic of China; 2Department of Pharmacy and Personalized Drug Therapy Key Laboratory of Sichuan Province, Sichuan Academy of Medical Sciences & Sichuan Provincial People’s Hospital, Chengdu 610072, People’s Republic of ChinaBackground: In vitro transcribed (IVT) mRNA has been applied as an alternative therapeutic molecule to plasmid DNA in the field of cancer therapy and biomedical research studies. mRNA-based therapy has demonstrated several advantages over its DNA counterparts. However, its further therapeutic application is largely restricted by delivery method.Methods: In this work, a liposome-protamine lipoplex (CLPP) was prepared to deliver IVT mRNA encoding survivin-T34A gene, forming a novel core-shell structured nanoparticle formulation (CLPP/mSur-T34A).Results: The prepared CLPP/mSur-T34A particle had an average size of 186.1±3.1 nm, displaying high mRNA transfecting and expression efficiency on C26 tumor cells through lipid rafts-mediated endocytosis. CLPP/mSur-T34A mRNA formulation demonstrated obvious therapeutic effects on various models of C26 colon cancer both in vitro and in vivo. Particularly, local and systemic administration of CLPP/mSur-T34A particle exhibited superior antitumor effect regarding its DNA plasmid counterpart with high safety.Conclusion: Our results indicated the high delivery capacity of liposome-protamine lipoplex and further suggested CLPP/mSur-T34A mRNA formulation to be a potential candidate for colon cancer therapy.Keywords: mRNA gene therapy, colon cancer, nonviral vector, systemic delivery